Chloroplast genome assembly, annotation, comparative genomics, and genetic diversity analysis of a vulnerable endemic species Lavandula maroccana Murb - Manosh Kumar Biswas; Jean Legeay; Khaoula Errafii; Imane Abbad; Pat Heslop-Harrison; Mohamed Hijri; Bulbul Ahmed (PLoS ONE, 2026)
Lavandula maroccana Murb., an endemic species of the western Mediterranean, is classified as vulnerable and was added to the International Union for Conservation of Nature (IUCN) Red List in 2020. We assembled and annotated the chloroplast genome and compared it with chloroplast genomes of five previously published Lavandula species. The assembled chloroplast genome of L. maroccana , spans 151,323 bp, and exhibits a typical quadripartite structure, consisting of an 82,861 bp large single-copy (LSC) region, a 17,452 bp small single-copy (SSC) region, and two 25,505 bp inverted repeat (IR) regions. The genome has a GC content of 38% and contains 110 unique genes, 37 tRNA genes, and 4 rRNA genes. A total of 37 perfect SSR motifs were identified, with most being mononucleotide repeats. Pentanucleotide and hexanucleotide repeats were absent as perfect motifs but were present as imperfect motifs at a lower frequency than other repeat types. AT-rich SSRs were more prevalent than GC-rich motifs. Palindromic and forward repeats were more frequent than complementary and reverse repeats. Nucleotide sequence diversity (Pi) values ranged from 0.004 ( atpH ) to 0.035 ( matK ), with protein-coding genes found to be under purifying selection. Phylogenomic analyses, based on the complete plastome sequences and the matK + trnL genes, revealed that intra- and inter-species diversity within Lavandula species. We compared the genomes, and their evolutionary relationships, and genetic structures with published chloroplast genomes from other species- L. maroccana , L. angustifolia , and L. dentata .